Level of knowledge of students in the graduation course in medicine at a private college in Piauí about electronic cigarettes (Research, Society and Development, 2023)
Electronic cigarettes have emerged as an alternative to conventional cigarettes, and are considered by some to be an alternative for those who want to quit smoking, although there is no proof of their effectiveness for this purpose. The objective of this study was to raise the level of knowledge about electronic cigarettes of students of the Graduate Course in Medicine at Centro Universitário Novafapi. This is a descriptive and analytical cross-sectional study, with 219 students, where a questionnaire was used with questions about the students' knowledge about the harmful effects of electronic cigarettes, later the data were analyzed with descriptive statistics.The analysis of the results showed that 73% identified themselves as female, age group ranged from 18 to 36 years, with a median of 22 years, with 170 students from the first to the sixth period and 49 students from the seventh to the twelfth period. Regarding smoking, 162 students said they had never smoked, 24 students were former smokers and 33 said they were smokers. The vast majority of students reported not having had contact with the topic during their undergraduate course. Likewise, the vast majority of students stated that they did not feel prepared to answer questions from patients about the use of electronic cigarettes. The results of this study point to the need for the curriculum to contemplate this subject in the training of future physicians, in order to enable them to guide their patients about the risks and benefits of using electronic cigarettes.